Cloud security: to prevent unauthorized access using an efficient key management authentication algorithm - Naveen Kumar, S; Nirmala, K (International Journal of Engineering and Technology, 2017)
Presently a-days Cloud registering is rising field in light of its Performance, high accessibility, easily. Information store is principle             future that cloud benefit gives to the huge association to store tremendous measure of information. Yet at the same time numerous              associations are not prepared to execute distributed computing innovation since absence of security. So the principle goal of this paper is to understand the security issues and to anticipate unapproved access in distributed storage, it should be possible with the assistance of an effective validation strategy by utilizing cross breed verification calculation to give security of the information in cloud and guarantee amending code to keep up the nature of administration. In any case, solid client confirmation that confines illicit access to the               administration giving servers is the foremost prerequisite for securing cloud condition